Disruption of global brain network topology in amnestic MCI: evidence from multimodal DTI and fMRI - Han, Yingmei; Bai, Xue; Li, Weiqing; Feng, Ze; Chu, Bingyuan; Yang, Ming; Shang, Qingqing; Zhang, Hanxi; Li, Xinlu; Wang, Feng (Frontiers in Neuroscience, 2025)
ObjectiveThis study aims to utilize multimodal neuroimaging techniques to simultaneously analyze global topological properties of white matter structural networks and resting-state functional networks in aMCI patients, comparing them with healthy controls. By conducting independent and integrative analyses of topological impairments in both networks, we seek to systematically characterize the multimodal network disruption patterns in aMCI.Methods45 aMCI patients and 42 healthy adults from the First Affiliated Hospital of Heilongjiang University of Chinese Medicine in Harbin, Heilongjiang Province, China, were enrolled. A case-control cross-sectional study was conducted. DTI and rs-fMRI data were collected for all participants. Global topological properties of structural and functional networks were constructed using PANDA and dpabi software and were calculated via graph-theoretical analysis in GRETNA software, followed by statistical comparisons between groups.ResultsIn patients with aMCI, the small-world (Cp, aCp, Lambda, aLambda) of the WM structural network were significantly higher than those in the HC group; Rich-club nodes showed redistribution, and the Rich-club coefficient was decreased; aEloc was significantly increased; the Assortativity index (r < 0) indicated disassortativity; the Hierarchy index (b > 0) exhibited a significant decrease in b within the sparsity range of 0.39∼0.4; the synchronization coefficient (s) was significantly reduced at sparsity levels ranging from 0.28 to 0.30. For the functional network, the small-world index aLp in the aMCI group was significantly lower than that in the HC group; Rich-club nodes showed redistribution, and the Rich-club coefficient was increased within a certain Degree range; aEg was significantly increased; the Assortativity index (r > 0) indicated assortativity; the Hierarchy index (b > 0) was observed within a specific sparsity range.ConclusionWe identified a “structure-function dissociation” in aMCI, where the structural network suffers from fragmentation and hub disruption, while the functional network compensates through rigid, hyper-localized reorganization with elevated local efficiency. This divergence reveals a core pathological mechanism of the disease.